Parametric investigation of soft-body penetration into parallel-ridged textured surfaces for tactile applications. (1st October 2016) - Wilde, T.J.; Schwartz, C.J.
Abstract: The tribological interactions between skin and textured surfaces has profound impact on both the tactile perception of the product being used, as well as the functionality of the product with regards to friction coefficient. Previous work has shown that parallel-ridged textures have vastly different friction coefficients with regards to the direction of skin sliding, and that penetration of the skin into the voids between ridges not only add contact area but also potential for interlocking. The ability to model skin penetration into textural elements would prove to be very useful for predicting friction; however, the mechanics of the problem are incredibly complex such that they rule out a closed-form analytical solution. The authors investigated soft-body penetration using a non-dimensional computational approach based on the elastic properties of skin, as well as the texture ridge geometry parameters, as well as the normal loading. Model results were verified experimentally. The model was applied to a number of different combinations of ridge parameters and it was found that the amount of penetration could be predicted very well using a simple exponential relationship among the nondimensional terms. Texture groove width and applied normal load played a dominant role in penetration. These results yield a quantitative mechanics model which can be integrated into an overarching frictional model to predict skin on texture behavior due to both adhesion and edge interlocking.